Qualitative and quantitative characterization of mutations and genetic diversity analysis in M2 populations of chilli (Capsicum annuum L.) - Nazarul Hasan; Sana Choudhary; Neha Naaz; Nidhi Sharma; Megha Budakoti; Dinesh Chandra Joshi; Mahendar Singh Bhinda; Rafiul Amin Laskar (Crop Design)
Mutations were induced through chemical mutagens to increase the genetic variability for the development of various mutants in M2 generation from genetic background of Capsicum annuum L. Main objective of this study was to identify mutants and to assess the genetic diversity in EMS, MMS, Cd(NO3)2 and Pb(NO3)2 induced M2 populations of Capsicum annuum L. Mutant phenotypes were categorized into sub-categories on the basis of their plant growth and morphological ​appearance, including plant habit, leaf, flower, fruit, and root. Mean value and genetic parameters such as genetic coefficient of variance, heritability and genetic gain were evaluated in quantitative traits. Inter-population differences were also carried out through analysis of variance. Enhanced heritability and genetic advance with high genetic coefficient variation in yield attributing traits provide an opportunity for the improvement of Capsicum annuum L. through phenotypic selection. In the present result, enhanced mean value at lower concentrations of mutagens in quantitative traits could endorse the improvement of mutant lines over their parental lines. Numbers of fruit per plant and 1000-seed weight were main priority traits in selection of high-yielding mutants and have a strong association with yield. The cluster analysis revealed that three divergent groups of Capsicum annuum L. with parent genotypes in an independent group showed high efficacy of mutagens. Genetic divergence among the cluster populations provides more opportunities to use chemical mutagens for inducing heritable changes in genetic material of Capsicum annuum L. and for further improvement of desirable traits. Mutants selected from treatments, including EMS1, EMS2, EMS3, MMS1 and MMS2, and Pb1, Pb2, and Cd1 could be used to develop an efficient and fast crop variety with desirable traits, and the mutagen EMS and MMS are more effective than Cd(NO3)2 and Pb(NO3)2.